2014
DOI: 10.2133/dmpk.dmpk-13-rg-104
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Differentiation of Human Induced Pluripotent Stem Cells into Hepatocyte-like Cells Retaining Drug Metabolizing Activity

Abstract: The use of human induced pluripotent stem (iPS) cells would be of great value for a variety of applications involving drug development studies. Several reports have been published on the differentiation of human iPS cells into hepatocyte-like cells; however, the cells were insufficient for application in drug metabolism studies. In this study, we aimed to establish effective methods for differentiation of human iPS cells into hepatocytes. Two human iPS cell lines were differentiated by addition of activin A, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…The hepatic differentiation protocol used in our study is similar to that in many reports (7,9). Our results of characterization of each differentiation stage by both immunofluorescent staining of key markers and expression levels of important genes are within the ranges of those observed in literature (7,9), suggesting that the differentiation process has been successful. The characterizations of the cells along differentiation stages and before encapsulation by staining ( Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The hepatic differentiation protocol used in our study is similar to that in many reports (7,9). Our results of characterization of each differentiation stage by both immunofluorescent staining of key markers and expression levels of important genes are within the ranges of those observed in literature (7,9), suggesting that the differentiation process has been successful. The characterizations of the cells along differentiation stages and before encapsulation by staining ( Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Many groups have reported monolayer differentiation of hiPSCs into hepatocyte-like cells (HLCs) and their ability to metabolize drugs (7)(8)(9). Nevertheless, hiPSC-derived HLCs are still considered immature in terms of many liver-specific gene expressions, functions, and cytochrome P450 (CYP) enzyme activities (7,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many researchers have reported the differentiation of human iPS cells into hepatocytes, which, like enterocytes, are important in drug pharmacokinetics (Si-Tayeb et al, 2010;Takayama et al, 2012;Ma et al, 2013). We have also established a method for the differentiation of human iPS cells into functional hepatocytes showing drug-metabolizing enzyme activities and inducibility (Kondo et al, 2014a). We found that histone deacetylase inhibitors promoted the hepatic differentiation of human iPS cells (Kondo et al, 2014b).…”
Section: Introductionmentioning
confidence: 89%
“…Similar to Chen et al, Kondo and co-workers generated hepatocytelike cells by sequential stimulation with growth factors [89] . However, while Chen and co-workers utilized IMDM medium from day 8 to 12, the Kondo protocol requires the use of Modified Laford medium from day 12 to 21.…”
Section: Generation Of Hepatocytes From Ips Cells Using Growth Factorsmentioning
confidence: 87%